INDONESIA CHARM OFFENSIVE: KEKUATAN BANTUAN LUAR NEGERI INDONESIA TERHADAP NEGARA PASIFIK SELATAN PADA ISU KEMERDEKAAN PAPUA BARAT - Angga Santa Gideon (Jurusan Ilmu Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Sriwijaya, 2021)
This article aims to discuss how foreign aid power to South Pacific countries on West Papua independence uses the Charm Offensive approach. Charm Offensive is a country's diplomacy method by providing foreign aid or investment to a recipient country to become an ally or support the country's political-economic motives. Charm Offensive requires high costs because it has to provide assistance and investment to other countries. However, the consideration is that this diplomacy method is very effective for countries that are indeed requesting assistance. Through this article, Charm Offensive will maintain its implementation through Indonesia's motives in providing foreign assistance to South Pacific countries. The motive was then relegated to take a deeper look at whether foreign assistance effectively quelled the rhetoric of South Pacific countries in supporting West Papua independence.